Development of Interactive Media Assisted by Google Sites Using Problem Based Learning Model in Grade V Elementary School - Sakinah, Fitri; Zainil , Melva; Ramadhan, Syahrul; Muhammadi , Muhammadi (Journal of Educational Sciences, 2025)
This research is motivated by the limited use of media in learning, which often leads to passive and disengaged students. One effort to address this issue is the development of interactive learning media using the Problem-Based Learning (PBL) model assisted by Google Sites. The aim of this study is to produce valid and practical interactive learning media and to determine its effectiveness in fifth-grade elementary school students. This research adopts the Research and Development (R&D) approach, using the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Data collection involved observations and interviews with teachers and students across three schools. The designed teaching materials were validated for content, implemented with students, and assessed for practicality and effectiveness through questionnaires and test instruments. Results show that the teacher practicality score averaged 94.69, and the student practicality score averaged 86.15, both in the "very practical" category. The student activity score was 84.40 ("very active"), learning outcomes averaged 89.39 ("effective"), and the N-Gain Score averaged 0.8 with a gain percentage of 75.67% ("effective"). These findings indicate that Google Sites-assisted learning media using the PBL model is valid, practical, and effective, and can serve as an alternative instructional tool in elementary education.